2021
DOI: 10.3389/fnut.2021.680870
|View full text |Cite
|
Sign up to set email alerts
|

Altered Serum Immunological and Biochemical Parameters and Microbiota Composition in Patients With AN During Realimentation

Abstract: Anorexia nervosa (AN) is a life-threatening psychiatric disorder with not well-described pathogenesis. Besides the genetic and sociological factors, autoimmunity is also considered to take part in AN pathogenesis. We evaluated general serological factors showing the physiological state of 59 patients with AN at hospital admission and their discharge. We detected the altered levels of some general biochemical and immunological parameters. We also detected decreased levels of appetite-regulating alpha-melanocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Our study observed decreased TSH and fT4 levels in patients with AN (but still in the normal range defined for normal BMI subjects) that did not increase even after treatment (Table ). Our results are in accordance with previous studies that have described altered thyroid function in AN patients. , Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism . As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study observed decreased TSH and fT4 levels in patients with AN (but still in the normal range defined for normal BMI subjects) that did not increase even after treatment (Table ). Our results are in accordance with previous studies that have described altered thyroid function in AN patients. , Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism . As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…19,20 Endocrine dysregulation is considered to be an adaptation to long-term starvation followed by the slowdown of energy metabolism. 21 As expected, these extensive hormonal changes were also projected in metabolism.…”
Section: ■ Discussionsupporting
confidence: 59%
“…Contrary to TNF-α and most previous adult studies, we found the cytokines IL-6 and IL-1β to be significantly reduced in our sample of adolescents with AN in comparison with HC and even remained so after short-term weight recovery. IL-1β and IL-6 were significantly increased in previous metanalyses (9, 10) and some recent publications (19, 47, 55); however, several current studies could not reproduce these findings or only reproduced them partially (10,25,47,56). Again, findings in adolescents were mixed (20,36,37).…”
Section: Cytokinesmentioning
confidence: 69%
“…Our results confirmed most previous research in terms of elevated proinflammatory TNF-α in adults with AN also in adolescents. This effect had been found in two large metanalyses (9,10) and several studies since (19,20,23,47). However, there is also a very well-controlled recent report challenging this finding (27), and adolescent findings are mixed (20,36,37).…”
Section: Cytokinesmentioning
confidence: 80%
“…Following the identification of IgM autoantibodies against alpha-melanocyte-stimulating hormone (α-MSH) in patients with anorexia nervosa by Fetissov et al 32 , several studies have been conducted to investigate the involvement of IgM autoantibodies in anorexia nervosa. Roubalova et al 47 found decreased levels of α-MSH and elevated levels of anti-α-MSH IgM in patients with anorexia nervosa, suggesting that the interaction between the immune system and gut bacterial diversity plays a role in the pathogenesis of anorexia nervosa. Although we did not analyze α-MSH in this study, the possibility that IgM acts as an autoantibody against α-MSH remains plausible.…”
Section: Discussionmentioning
confidence: 99%